Proteins bound to rubber particles and sensitivity to the tapping panel dryness in Hevea brasiliensis - Okoma K M; Ake S; Dian K; Sangare A (Journal of Rubber Research, 2007)
DL
Keywords: Cote dIvoire; Proteins; Rubber particles; Sensitivity; Tapping panel dryness